The Alamo - Smith, Roland 1951-; Spradlin, Michael P. (Sleeping Bear Press, 2013)
"When Quest (Q) and his stepsister Angela head to Texas for their parents' concert, they discover traces of the terrorist group Ghost Cell in the Lone Star state"-Provided by publisher
Keywords: Spies; Terrorism; Stepfamilies; Musicians; Mystery and detective stories; Alamo (San Antonio, Tex.); Jugendbuch